2020
DOI: 10.1115/1.4045438
|View full text |Cite
|
Sign up to set email alerts
|

Investigation Into the Phenomenon of Flow Deviation in the S-Shaped Discharge Passage of a Slanted Axial-Flow Pumping System

Abstract: A remarkable flow deviation phenomenon exists in the S-shaped discharge passage of a slanted axial-flow pumping system. In order to reveal the characteristics and development process of the deviating flow, numerical simulation was performed for a 15 deg slanted axial-flow pumping system, and the deviating flow was measured on an experimental rig. The details of the deviating flow in the S-shaped discharge passage were obtained. A kind of “unwinding” flow structure similar to that of DNA in biology is found in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…And the low-frequency pressure fluctuation mechanism of pump unit under stall condition was revealed. Wang et al [8] investigated the flow deviation phenomenon in S-shaped flow passage in a slanted axial-flow pumping station, the 'unwinding' flow structure was discovered and the development of 'unwinding' structure in different locations of Sshaped discharge passage was revealed.…”
Section: Introductionmentioning
confidence: 99%
“…And the low-frequency pressure fluctuation mechanism of pump unit under stall condition was revealed. Wang et al [8] investigated the flow deviation phenomenon in S-shaped flow passage in a slanted axial-flow pumping station, the 'unwinding' flow structure was discovered and the development of 'unwinding' structure in different locations of Sshaped discharge passage was revealed.…”
Section: Introductionmentioning
confidence: 99%
“…Domestic and foreign scholars have done a lot of research on the slanted axial-flow pump; for example, Zhang et al [1] numerically simulated the cavitation performance of the slanted axial-flow pump under different working conditions and explored the causes of the collapse of the cavitation performance of the slanted axial-flow pump. Wang et al [2] found that there was a flow deviation phenomenon in the S-shaped channel of the 15 • slanted axial-flow pump, and carried out numerical simulation research and field measurement on the test bench to clarify the mechanism of this phenomenon. Yang et al [3], based on Reynolds-averaged Navier-Stokes equations and RNG k-ε turbulence model, studied the three-dimensional fluid flow in a slanted axial-flow pump, analyzed the velocity distribution and stress distribution of the flow field in the slanted axial-flow pump under different working conditions, and found that they were in good agreement with the experimental study.…”
Section: Introductionmentioning
confidence: 99%
“…Pump devices are generally divided into vertical, slanted and tubular pump devices according to the flow passage form. Due to the extensive use of axial flow pump devices, many experts have studied the optimization and design of various types of pump device [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%